2018
DOI: 10.15561/20755279.2018.0502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the leg and back strength of the serve and tennis players to the serve throwing speed and agility

Abstract: Background and Study Aim:The aim of this study was to examine the effect of leg and back strength on serve throwing speed and agility of 19-23 year old male tennis players who are studying at university. Material and Methods: Twelve male tennis players, aged between 19 and 23, who were studying at university in Kayseri participated in the study voluntarily. Individuals who played tennis for at least 5 days per week participated in the study and leg and back strength measurements and their relation with the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…There are several studies concerning the correlation between HGS, BS, and LS in adults. Kaya et al (2018) reported a high correlation between HGS and LS (r=0.863, p <0.001). Koley et al (2010) found a statistically significant correlation between LS and BS in male cricketers (p <0.05).…”
Section: Discussionmentioning
confidence: 97%
“…There are several studies concerning the correlation between HGS, BS, and LS in adults. Kaya et al (2018) reported a high correlation between HGS and LS (r=0.863, p <0.001). Koley et al (2010) found a statistically significant correlation between LS and BS in male cricketers (p <0.05).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the findings mentioned above, evidence to the contrary exists. Research indicated that lower-body strength was not only associated with service speed [ 2 , 5 ] but that knee extension peak torque was the only variable to significantly affect ball placement [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contemporary tennis, predicting variables involved in players’ performance could help coaches and physical trainers design an effective training plan in order to enhance sport-specific performance. It is well-established that tennis matches require strength, cardiovascular endurance, speed and power to perform high stroke velocities, together with a complex interaction of technical and tactical skills [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Therefore, it is possible to infer that one predominant factor cannot define a successful performance.…”
Section: Introductionmentioning
confidence: 99%
“…Kovacs and Ellenbecker, (2011) claim that the tennis serve is a challenging motion that calls for athletes to coordinate their upper and lower limbs and joints in order to gather all forces generated on the ground and transfer them to the ball. Studies have shown a strong correlation between tennis serve speed and leg strength (Kaya et al, 2018). Reid et al (2012) found that powerful performance of lower limbs can improve the racket's capacity to support speed.…”
Section: Introductionmentioning
confidence: 99%